2021
DOI: 10.1038/s41467-021-27599-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrated single-cell transcriptome analysis reveals heterogeneity of esophageal squamous cell carcinoma microenvironment

Abstract: The tumor microenvironment is a highly complex ecosystem of diverse cell types, which shape cancer biology and impact the responsiveness to therapy. Here, we analyze the microenvironment of esophageal squamous cell carcinoma (ESCC) using single-cell transcriptome sequencing in 62,161 cells from blood, adjacent nonmalignant and matched tumor samples from 11 ESCC patients. We uncover heterogeneity in most cell types of the ESCC stroma, particularly in the fibroblast and immune cell compartments. We identify a tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 64 publications
4
78
0
Order By: Relevance
“…Cluster 5 uniquely expressed a variety of heat-shock proteins (HSPA1B, HSPB1, and HSPA1A), and cytokines. (CD52, CCL5, and IL32), and was resemble with a group of dysfunctional CD8 T cells recently identified in melanoma, esophageal squamous cell cancer and liver cancer (21)(22)(23). It is reported that extracellular HSPs can trigger immune responses.…”
Section: Characterization Of Single-cell Expression Profiles For Nk/t...mentioning
confidence: 53%
“…Cluster 5 uniquely expressed a variety of heat-shock proteins (HSPA1B, HSPB1, and HSPA1A), and cytokines. (CD52, CCL5, and IL32), and was resemble with a group of dysfunctional CD8 T cells recently identified in melanoma, esophageal squamous cell cancer and liver cancer (21)(22)(23). It is reported that extracellular HSPs can trigger immune responses.…”
Section: Characterization Of Single-cell Expression Profiles For Nk/t...mentioning
confidence: 53%
“…Heterogeneity was found in most ESCC interstitial cell types, particularly between fibroblasts and immune cells. Also, tumor-specific CST1 + myofibroblast subpopulations had been identified to have prognostic values and potential biological significance ( 95 ). Also, the main association framework between cancer cells and various non-cancer cells in TME has been established via single-cell transcriptome sequencing, which contributes to the further investigation of ESCC progression and prognosis ( 96 ).…”
Section: The Role Of Tumor Microenvironment In Esophageal Squamous Ce...mentioning
confidence: 99%
“…Macrophages were clustered into five subsets. Among the five macrophage subsets, Mac_1, Mac_2 and Mac_3 expressed higher anti-inflammatory “M2” -related genes in Mac_C, with Mac_5 expressing M2-like genes ( 38 ).…”
Section: Scs Applications and Achievements In Ecmentioning
confidence: 99%
“…Three classes of CD4+ T cells were identified via SCS, and it was found that CD4_1 upregulates TIGIT expression in tumors, CD4_2 expresses PD-1 (encoded by PDCD1) exclusively in tumors, and CD4_3 showed tumor-specific TIGIT and CD96 expression. In addition, both CD4_1 and CD4_2 were found to express high levels of CTLA-4 in tumors ( 38 ). Wu et al.…”
Section: Scs Applications and Achievements In Ecmentioning
confidence: 99%